The Distribution of the Agentive Nominalizer of the Suffixes {-er} and {-an} - Denistia, Karlina; Alip, Francis Borgias (Journal of Language and Literature, 2014)
This study focuses on the suffixes {–er} and {-an} because these suffixes are the most commonly used suffixes in daily life and thus really productive. There are three problems formulated for this topic: (1) What are the characteristics of stems receiving suffixes {–er} and {-an}? (2) What meanings are introduced by suffixes {–er} and {–an}? (3) What are the distributions of the allomorphs of suffixes {–er} and {-an}? The data of this study are morphemes and affixes. Hornby’s Oxford Advanced Learner’s Dictionary (year of 2000) is used. Finally, the present researcher found that the suffixes {–er} and {an} are attached to certain verbs, adjectives, and nouns. The suffix {-an} are not attached to verbs. The suffix {-er} is mostly attached to transitive verbs to create three possibilities of meaning. There is only one meaning of the suffix {–er} when it is attached to an adjective, and eight meanings of the suffix {–er} when it is attached to certain nouns. For suffix {-an}, there are three meanings when it is attached to adjectives and five meanings when it is attached to nouns. There are two meanings of the suffix {-an} when it is attached to nouns. The allomorph of the suffix {-er} are –or, -eer /ɪər/, and –ier /ɪər/, while the allomorphs of the suffix {-an} are –ian /ʃn/, -ian /ɪən/, and –ean /ɪən/. Keywords: morpheme, derivational suffixes, an agentive nominalization, stem, allomorph